Universal Childcare and Longer-Run Effects on Parental Health and Behaviors: Evidence from a Canadian Universal Child Care Program - Laetitia Lebihan; Catherine Haeck; Pierre Lefebvre; Philip Merrigan (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2015)
In this paper, we study the long-run impact of a universal child care policy in Quebec on parental health and parenting practices. Using data from the National Longitudinal Survey of Child and Youth, we follow treated families for more than 9 years and investigate the impact well beyond the first few years of the policy. A non-experimental evaluation framework based on multiple pre- and post-treatment periods is used to estimate the policy effects. We show that the policy increased mothers' depression scores with preschool children as well as scores of inappropriate parenting behavior. The policy increased hostile and aversive parenting and reduced positive interaction and consistent parenting. However, negative effects of the program on parental behaviors vanish when the child is in school. Moreover, we find that this pattern persists even ten years after the implementation of the reform.
Keywords: I31; J18; J20; 330; universal child care; parental health and behaviors; longer-run effects; child care policy; natural experiment